Fermentation process of apple juice investigated by NMR spectroscopy. (October 2018) - Cusano, Erica; Simonato, Barbara; Consonni, Roberto
Abstract: Cider is a slightly alcoholic beverage and is an important and promising segment of the fruit industry. In this study, a still cider produced by fermentation of apples juice was investigated. A simultaneous characterization of bioactive compounds in apple juice and the intermediate products of the cidermaking process was performed for the first time using Nuclear Magnetic Resonance spectroscopy. Alongside sugar consumption, a progressive increase in trigonelline, chalcone, fumarate, caffeic acid, uracil, tyrosol and xanthine content was detected during the alcoholic fermentation process. Of note was the relatively high tyrosol content which imparts health benefits in the cider. The concomitant changes in phenol, amino acid and organic acid (malic, lactic, quinic, pyruvic, citric and succinic) content, was important when monitoring the fermentation process and assessing quality control of the final product. Highlights: Apple juice fermentation investigated for the first time by NMR spectroscopy. Evolution of bioactive compounds monitored during cider fermentation by NMR. Uracil and xantine detected in apple cider for the first time. Phenolic compounds detected by NMR at the end of fermentation process.